Iron(III) promoted oxidative annulation of benzylic C-H bonds in (α-amino)arylacetic acids for synthesis of 4-aryl pyrrolo[1,2-a]quinoxalines - Tuan Hoang Ho; Tung Thanh Nguyen; Tran Hoang Bao Ngo; Nam Thanh Son Phan (Vietnam Journal of Science, Technology and Engineering, 2023)
Using amino acids for synthesis of heterocycles is a synthetically promising field. However, developing the practical methods for transformations of amino acids into heterocycles is still challenging. Given that alpha amino acids are abundant or easily prepared, herein we report a method for annulation of benzylic C-H bonds in derivatives of 2-phenylglycine with 1-(2-nitroaryl) pyrroles. The reactions proceeded well in the presence of iron(III) acetylacetonate catalyst and potassium carbonate base. Scope of pyrrolo[1,2-a]quinoxalines was studied. Regardless of electronic properties of substituents, the pyrrolo[1,2-a]quinoxaline de- rivatives were successfully isolated, as yields varied from 42% to 52%. Pyrrolo[1,2-a]quinoxalines substituted with heterocycles at C4 positions as pyridine and thiophene were competent substrates. Reaction mechanism was proposed to start with a decar- boxylative/deaminative sequence of 2-phenylglycine to afford benzaldehyde. The iron catalyst was presumed to facilitate the re- duction of 1-(2-nitroaryl)pyrroles to furnish the corresponding aniline. Imine condensation followed by cyclisation and oxidation would yield the pyrrolo[1,2-a]quinoxaline. Our method would offer a convenient tactic to transform abundant alpha amino acids into synthetically useful heterocycles.